Diaqua-2κ2O-bis(μ-1-oxido-2-naphthoato)-1:2κ3O1,O2:O2′;2:3κ3O2:O1,O2′-bis(1-oxido-2-naphthoato)-1κ1O2,O2;3κ2O1,O2-hexapyridine-1κ2N,2κ2N,3κ2N-trimanganese(II/III) pyridine disolvate dihydrate - Daqi Wang; Dacheng Li; Yuting Chen; Hua Yang (Acta Crystallographica Section E, 2008)
The title complex, [Mn3(C11H6O3)4(C5H5N)6(H2O)2]·2H2O·2C5H5N, is a trinuclear mixed oxidation state complex of overline1 symmetry. The three Mn atoms are six-coordinated in the shape of distorted octahedra, each coordinated with an O4N2 set of donor atoms, where the ligands exhibit mono- and bidentate modes. However, the coordination of the MnII ion located on the inversion centre involves water molecules at two coordination sites, whereas that of the two symmetry-related MnIII ions involves an O4N2 set of donor atoms orginating from the organic ligands. Intramolecular C—H...π interactions between neighbouring pyridine ligands stabilize this arrangement. A two-dimensional network parallel to (001) is formed by intermolecular O—H...O hydrogen bonds.